Circumsolar irradiance modelling using libRadtran and AERONET data - Abreu, Edgar F.M. (2020)
The aperture angle of pyrheliometers is greater than the limit angle of the solar disk, which leads to a contribution of circumsolar radiation to the measurements of direct normal irradiance (DNI). On the other hand, since Concentrating Solar Power (CSP) technologies have, generally, a lower aperture angle with respect to pyrheliometers, it is important to determine the fraction of circumsolar irradiance present in the DNI measurements as well as its angular distribution to provide accurate information for sizing and operation of CSP systems. In this work, the monochromatic circumsolar irradiance (at 675 nm) is modelled using libRadtran and AERONET data at Évora, Portugal for selected cases representing the 1st, 25th, 50th and 75th percentiles of the aerosol optical depth (AOD) measurements distribution at 675 nm and a maximum value of AOD registered during a Saharan dust outbreak in February 2017 in Portugal. The AERONET products used were the columnar values of water vapor content, aerosol optical depth (AOD) and aerosol phase function. Since there are no measurements of circumsolar irradiance at Évora, the assessment of the model output accuracy was done through a comparison of both the modelled DNI from the solar disk only and the DNI including the circumsolar contribution against measurements from a pyrheliometer included in a meteorological station installed at the same location. The mean bias error and the root mean square error were found to be lower for the DNI with the circumsolar contribution, thus validating the modelling approach of circumsolar irradiance.